Digital transformation of construction training at the university in conditions of using an electronic educational resource for the discipline «Technical expertise and technology for building reconstruction» - Olga A. Bessonova; Ludmila I. Mironova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the context of the digital transformation of engineering and construction training, the paper discusses an electronic educational resource (EER), implemented by means of BIM design technology (Building Information Modelling, information model of an object) for studying the discipline «Technical expertise and technology of building reconstruction» at the Institute of Construction and Architecture of the Ural Federal University. The relevance of the study can be explained by the fact that insufficiently developed Russian regulatory framework and the limited distribution of domestic computer-aided design programs slow down the digital transformation of both the construction industry and the education system. The aim of the research is to describe the possibilities of electronic educational media using automatic design systems in the development of information models of reconstructed objects for the training of civil engineering bachelors, as well as to analyze regulations for overseeing the field of information design. To reach the aim of the study, the following objectives were achieved: the terminology has been clarified for the information model of the object for use in the learning process; the analysis of regulatory documents was carried out on the topic of digital modeling; examples of the use of BIM-technologies in the reconstruction of construction projects were given; an assessment was made of the significance of the technology considered in the process of training graduates for the construction industry. The object of the study is the process of training future construction workers at the Department of Industrial, Civil Engineering and Real Estate Expertise of the Ural Federal University using an EER and digital design methods for the reconstruction of construction projects. The subject of the study is the development of future civil engineers’ professional competence in the field of technical expertise and technology for the reconstruction of buildings using EER, implemented by means of BIM-design technology. The result is the development of educational and methodological support for the discipline «Technical Expertise and Technology of Building Reconstruction», based on the use of digital technology «Augmented Reality», which is aimed at developing bachelor skills for designing digital models of buildings and effectively use acquired knowledge for planning and distribution of resources (material, financial, labor) when organizing reconstruction work. The scientific novelty of the research consists of identifying the social significance of BIM design technology for the purpose of reconstruction of construction sites; developing the structure of the content of the basic block of bachelor training in order to develop professional competence in the field of reconstruction of construction projects in the digital educational environment of the university; the development of modern educational and methodological support for the educational process, taking into account the digital transformation of engineering training, the use of which will allow graduates to develop the necessary professional competence to work in an information and design environment. The practical significance is in the application of the developed EER in the learning process, which contributes to the development of students’ interest, forms the necessary professional competence of future civil engineers, increasing their competitive qualities for future work in the information and design environment.